2016
DOI: 10.1021/jacs.6b04339
|View full text |Cite
|
Sign up to set email alerts
|

Streamlined Total Synthesis of Uncialamycin and Its Application to the Synthesis of Designed Analogues for Biological Investigations

Abstract: From the enediyne class of antitumor antibiotics, uncialamycin is among the rarest and most potent, yet one of the structurally simpler, making it attractive for chemical synthesis and potential applications in biology and medicine. In this article we describe a streamlined and practical enantioselective total synthesis of uncialamycin that is amenable to the synthesis of novel analogues and renders the natural product readily available for biological and drug development studies. Starting from hydroxy- or met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 64 publications
2
79
0
4
Order By: Relevance
“…The TNMs are extremely potent against a broad spectrum of cancer cell lines, with subnanomolar 50% inhibitory concentrations (IC 50 s). For example, TNM A is more potent than UCM, particularly against breast cancer cell lines (Table 1A); UCM is currently in preclinical development as an ADC (Chowdari et al, European patent application WO 2013122823 A1) (44). Most impressively, as exemplified with the SKBR-3 breast cancer cell line, TNM A exhibited more rapid and more complete cell killing than AFP and AP-3 (Tables 1B and C), thereby minimizing the development of potential drug resistance (45, 46), supporting the wisdom of exploiting the TNMs as payload candidates for the next generation of anticancer ADCs.…”
Section: Resultsmentioning
confidence: 99%
“…The TNMs are extremely potent against a broad spectrum of cancer cell lines, with subnanomolar 50% inhibitory concentrations (IC 50 s). For example, TNM A is more potent than UCM, particularly against breast cancer cell lines (Table 1A); UCM is currently in preclinical development as an ADC (Chowdari et al, European patent application WO 2013122823 A1) (44). Most impressively, as exemplified with the SKBR-3 breast cancer cell line, TNM A exhibited more rapid and more complete cell killing than AFP and AP-3 (Tables 1B and C), thereby minimizing the development of potential drug resistance (45, 46), supporting the wisdom of exploiting the TNMs as payload candidates for the next generation of anticancer ADCs.…”
Section: Resultsmentioning
confidence: 99%
“…Scheme 2summarizes the strategy employed by the Corey group in their total synthesis of maytansine (105), the first to be achieved of this molecule in 1980. [80b] Scheme 2Aindicates, in retrosynthetic format, the chartered synthetic strategy for the synthesis as it evolved, while Scheme 2B provides details for its execution.…”
Section: Maytansinementioning
confidence: 99%
“…A) Retrosynthetic disconnections;a nd B) total synthesis (1992, Kishi et al). [89] Angewandte Chemie Reviews retrosynthetic disconnections and defined building blocks indicated in Scheme 11 A, the streamlined total synthesis of uncialamycin [105] starting material 254.T his scalable synthesis has been employed to produce,b esides uncialamycin, numerous designed analogues,t wo of which (i.e., 264 and 265)a re highlighted in Scheme 11 Ct ogether with their cytotoxicities against anumber of cancer cell lines. [105] 4.8.…”
Section: Uncialamycinmentioning
confidence: 99%
“…Our first total synthesis delivered the natural substance in racemic form and allowed its full relative stereochemical assignment, while our second and asymmetric synthesis delivered its natural enantiomeric form and proved its absolute configuration . In our most recent total synthesis of uncialamycin we discovered and employed a much more efficient method for the construction of its anthraquinone moiety and developed a streamlined process for its production (22 linear steps, 11 % overall yield) . Summarized in Figure [from building blocks J – N and intermediates (+)‐ 74 –(+)‐ 77 ], this strategy was employed for the construction of numerous analogues of uncialamycin, some with low picomolar potencies against a variety of tumor cells.…”
Section: Applications Of Total Synthesis To Potential Cancer Therapiesmentioning
confidence: 99%